Shift workers have similar leisure-time physical activity levels as day workers but are more sedentary at work - Gerben Hulsegge; Nidhi Gupta; Andreas Holtermann; Marie Birk Jørgensen; Karin I Proper; Allard J van der Beek (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVE: Physical inactivity has been hypothesized as an underlying factor for the association between shift work and adverse health outcomes. We compared leisure-time and occupational physical activity and sedentary behavior between day, night, and non-night shift workers. METHODS: We identified 612 day workers, 139 night shift workers and 61 non-night shift workers aged 18-65 years (54% men) in two Danish studies: the New method for Objective Measurements of physical Activity in Daily living (NOMAD) and the Danish Physical ACTivity cohort with Objective measurements (DPhacto) between 2011-2013. Sedentary behavior, light, and moderate-to-vigorous physical activity were measured using an accelerometer. Physical activity was expressed as percentage of leisure and work time spent in each activity. Linear regression analyses were used to test differences in physical activity and sedentary behavior between day, night, and non-night shift workers. RESULTS: No differences in leisure-time sedentary behavior and physical activity were observed between day and shift workers (P>0.05). Non-night shift workers spent 7.2% [95% confidence interval (95% CI) 2.3-12.1) more time in occupational sedentary behavior than day workers and 5.9% (95% CI -10.1- -1.7) and 1.9% (95% CI -3.7- -0.2) less time in occupational light and moderate-to-vigorous physical activity, respectively. Compared to day workers, night shift workers spent 4.3% (95% CI 2.4-6.1) more time at work in uninterrupted sedentary periods of ≥30 minutes. CONCLUSIONS: Shift workers had similar leisure-time physical activity patterns as day workers, but were more sedentary at work. Future research should elucidate whether occupational physical inactivity and sedentary behavior contributes to shift work-related adverse health effects.